Discovery of 3-Arylcoumarin-tetracyclic Tacrine Hybrids as Multifunctional Agents against Parkinson’s Disease - Sashidhara, Koneni V. (American Chemical Society, 2014)
[Image: see text] A series of multifunctional directed 3-arylcoumarin-tetracyclic tacrine derivatives was designed and synthesized for the treatment of Parkinson’s disease (PD). A number of derivatives (18, 19, 20, 21, and 24) demonstrated significant reduction of aggregation of “human” alpha-synuclein (α-synuclein) protein, expressing on transgenic Caenorhabditis elegans (C. elegans) model NL5901. Moreover, compounds 16, 18, and 24 also exhibited good antioxidant properties and significantly increased the dopamine (DA) content in N2 and NL5901 strains of C. elegans. Interestingly, the protective efficacy of these hybrids seems to be mediated via activation of longevity promoting transcription factor DAF-16. In addition, molecular modeling studies have evidenced the exquisite interaction of most active compounds 18 and 24 with α-synuclein protein. Taken together, the data indicate that the derivatives may be useful leads against aging and age associated PD.